EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR RIAS WAJAH SEHARI-HARI PADA MATA PELAJARAN DASAR KECANTIKAN SISWA KELAS X TATA KECANTIKAN DI SMK NEGERI 1 BERINGIN - Lusina Rajagukguk, Semi; Wahidah, Siti; Astrid Sitompul; Nurhayati; Asrah Rezki Fauzani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of the Make a Match learning model in improving students' learning outcomes in the daily makeup topic of the Basic Beauty subject for Grade X Beauty Program students at SMK Negeri 1 Beringin. The study employed a quantitative method using a quasi-experimental approach with a One Group Pretest–Posttest Design. The research sample consisted of 30 students selected using the total sampling technique. Data were collected through pretest and posttest learning achievement tests. The data were analyzed using the Shapiro–Wilk normality test, N-Gain test, and Paired Sample t-Test with the assistance of IBM SPSS Statistics. The results showed that the mean pretest score of 52.16 increased to 80.00 in the posttest. The normality test indicated that the data were normally distributed, with significance values of 0.451 for the pretest and 0.424 for the posttest. The mean N-Gain score was 0.5666, which was classified as a moderate improvement with a moderately effective level of effectiveness. Furthermore, the Paired Sample t-Test yielded a significance value (Sig. (2-tailed)) of < 0.001, indicating a statistically significant difference between students' learning outcomes before and after the implementation of the Make a Match learning model. Therefore, it can be concluded that the Make a Match learning model was moderately effective in improving students' learning outcomes in the daily makeup topic of the Basic Beauty subject for Grade X Beauty Program students at SMK Negeri 1 Beringin.